Multiplexed SNP genotyping using nanobarcode particle technology - Sha, Michael Y; Walton, Ian D; Norton, Scott M; Taylor, Micah; Yamanaka, Mark; Natan, Michael J; Xu, Chongjun; Drmanac, Snezana; Huang, Steve; Borcherding, Adam; Drmanac, Radoje; Penn, Sharron G (Analytical and bioanalytical chemistry, 2006)
Single-nucleotide polymorphisms (SNP) are the most common form of sequence variation in the human genome. Large-scale studies demand high-throughput SNP genotyping platforms. Here we demonstrate the potential of encoded nanowires for use in a particles-based universal array for high-throughput SNP genotyping. The particles are encoded sub-micron metallic nanorods manufactured by electroplating inert metals such as gold and silver into templates and releasing the resulting striped nanoparticles. The power of this technology is that the particles are intrinsically encoded by virtue of the different reflectivity of adjacent metal stripes, enabling the generation of many thousands of unique encoded substrates. Using SNP found within the cytochrome P450 gene family, and a universal short oligonucleotide ligation strategy, we have demonstrated the simultaneous genotyping of 15 SNP; a format requiring discrimination of 30 encoded nanowires (one per allele). To demonstrate applicability to real-world applications, 160 genotypes were determined from multiplex PCR products from 20 genomic DNA samples.